Соціальна відповідальність бізнесу в Україні: проблеми та шляхи вирішення - Мороз, О.С. (Економіка промисловості, 2013)
Стаття присвячена характеристиці соціальної відповідальності бізнесу, висвітленню соціальних аспектів розвитку бізнесу на прикладі металургійної промисловості України, дослідженню стану соціально відповідального бізнес-середовища в країні та окремих мотивів, які змушують та заохочують роботодавців вести соціально орієнтований бізнес. Запропоновано заходи, спрямовані на створення системи узгодження інтересів усіх учасників соціального діалогу та побудову соціально відповідального бізнес-середовища і посилення уваги до соціальних аспектів розвитку бізнесу в Україні. Статья посвящена характеристике социальной ответственности бизнеса, освещению социальных аспектов развития бизнеса на примере металлургической промышленности Украины, исследованию состояния социально-ответственной бизнес-среды в стране и отдельных мотивов, которые заставляют и поощряют работодателей проводить социально-ориентированный бизнес. Предложены меры по созданию системы, направленной на согласование интересов всех участников социального диалога и построение социально-ответственной бизнес-среды и усиление внимания к социальным аспектам развития бизнеса в Украине. The experience of leading developed countries dominated by the principles of market economy shows that today the creation offavourablebusiness environment and attractive conditions for investors by a state is impossible without effective social-oriented business that relies on a comprehensive system of protection of the interests of all participants of economic relations guaranteed by the state and perceived by society as a whole. At the same time, some social aspects of the business environment in Ukraine, including the application features of process harmonization of conflict of interest and ensuring the mutual cooperation of the state (regional) government, business owners (employers) and worker (trade unions), in our opinion, require further investigation. The aim of the article is to highlight some issues related to the social aspects of business development, particularly in industry, and their possible solutions. Analysis of specific existing interpretations of the concept of socially responsible business has shown that the implementation of social policies based on the business logic of market economy in the long run creates a favorable social environment and therefore provides the possibility of gaining well-established profits. In order to develop socially responsible business environment the paper presents proposals for the formation of uniform business rules that are socially responsible to salaried staff and society as a whole, as well as the assessment of CSR and its criteria, the specification of reconciling the interests of social dialogue, and social mechanism for monitoring compliance commitments and responsibilities of the parties.